Iatrogenic Pseudoaneurysm After Continuous Adductor Canal Block. Issue 9 (1st November 2016) - Cappelleri, Gianluca; Molinari, Pietro; Stanco, Antonella
Abstract : No major complications have been associated with the ultrasound-guided continuous adductor canal block (cACB). We present a case of iatrogenic pseudoaneurysm in a branch of the superficial femoral artery in a 44-year-old patient after a cACB for knee surgery. Both anesthesia and surgery were completed uneventfully. The postoperative day 3 examination showed a complete quadricep impairment and a large hematoma in a medial-anterior part of the thigh, and laboratory tests reported hemoglobin = 7.2 g dL −1 . The computed tomography scan revealed the pseudoaneurysm (16 × 16 × 18 mm) that was successfully embolized after selective catheterization. The patient was discharged regularly on postoperative day 12.